Development of Website-Based Stunting Prevention Educational Media Services (Case Study: UPT Puskemas Tirto Pekalongan) - Kusumasari, Dinita; Subhiyakto, Egia Rosi (Advance Sustainable Science, Engineering and Technology, 2024)
UPT Puskesmas Tirto is a public health center located in the West Pekalongan sub-district that provides maternal and child health poly services.Â  This poly provides educational services related to the problem of stunting in children through Posyandu activities. However, providing educational services is less effective and efficient because some parents do not have much time to attend counseling so information is not conveyed properly. This research aims to optimize the provision of educational services to parents, prospective mothers, and young women through the use of information technology by developing a website-based stunting prevention educational media service using the ReactJs framework. The development process of this research is carried out by prototyping method. Based on the results of testing using the Blackbox method, it shows that the main features such as nutrition check services, consultation services with Puskesmas nutritionists, and literacy services in the form of articles in the application can run well according to their functions in providing stunting prevention information with 100% results.